2010
DOI: 10.1111/j.1574-6968.2010.01933.x
|View full text |Cite
|
Sign up to set email alerts
|

Genome mining inAmycolatopsis balhimycinafor ferredoxins capable of supporting cytochrome P450 enzymes involved in glycopeptide antibiotic biosynthesis

Abstract: Ferredoxins are required to supply electrons to the cytochrome P450 enzymes involved in cross-linking reactions during the biosynthesis of the glycopeptide antibiotics balhimycin and vancomycin. However, the biosynthetic gene clusters for these antibiotics contain no ferredoxin- or ferredoxin reductase-like genes. In a search for potential ferredoxin partners for these P450s, here, we report an in silico analysis of the draft genome sequence of the balhimycin producer Amycolatopsis balhimycina, which revealed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 46 publications
0
3
0
Order By: Relevance
“…In some cases, P450s are co-transcribed with their immediate redox partner, typically an Fe-containing ferredoxin, although this is not always the case and many instances have been reported where (multiple) bacterial P450s can accept electrons from a range of endogenous redox partners within the parent bacterial strain. [21][22][23][24] Even though many P450s identied in bacteria can be assigned to a specic biosynthetic cluster, this does not always make the identication of their biosynthetic role a facile process. One representative example of such a scenario is seen in clavulanic acid biosynthesis, where P450 cla (Orf10) has been identied as a part of the gene cluster for more than 15 years.…”
mentioning
confidence: 99%
“…In some cases, P450s are co-transcribed with their immediate redox partner, typically an Fe-containing ferredoxin, although this is not always the case and many instances have been reported where (multiple) bacterial P450s can accept electrons from a range of endogenous redox partners within the parent bacterial strain. [21][22][23][24] Even though many P450s identied in bacteria can be assigned to a specic biosynthetic cluster, this does not always make the identication of their biosynthetic role a facile process. One representative example of such a scenario is seen in clavulanic acid biosynthesis, where P450 cla (Orf10) has been identied as a part of the gene cluster for more than 15 years.…”
mentioning
confidence: 99%
“…In this intervening time period, the Robinson group continued to take steps forward, first exploring potential natural redox partners for the Oxy enzymes within the vancomycin expression strain. [30] Their studies also showed that the presence of chlorine atoms in the peptide diminished the in vitro activity of OxyB van , apparently through a reduction in binding affinity. [31] As previous studies had showed a marked preference for hexapeptide cyclisation over heptapeptides, [27] and combined with the halogenated peptide turnover data, this led to the hypothesis that the activity of OxyB would occur on module 6 at the hexapeptide stage.…”
Section: Chembiochemmentioning
confidence: 99%
“…However, it would in fact be more than 10 years after the first reports of in vitro OxyB activity before the activity of the second enzyme in the cascade, OxyA, would be demonstrated. In this intervening time period, the Robinson group continued to take steps forward, first exploring potential natural redox partners for the Oxy enzymes within the vancomycin expression strain [30] . Their studies also showed that the presence of chlorine atoms in the peptide diminished the in vitro activity of OxyB van , apparently through a reduction in binding affinity [31] .…”
Section: Figurementioning
confidence: 99%